Airborne early warning system concepts - Long, Maurice W. (SciTech Publishing, 2004)
This book addresses the concept of Airborne Early Warning (AEW) systems, their capabilities and limitations, and areas in which they can be improved. It was written for systems-oriented people such as program managers, users, system integrators, and designers. Airborne platforms, sensors, and overall system requirements are discussed in broad terms. Radar is dealt with separately because of its unchallenged, all-weather capability for the detection of targets at long range. The book was written to provide an understanding of the status of AEW concepts without using complex mathematics. There are, however, sections that include details for specialists in such important areas as sidelobes due to antenna and airframe interactions, small target detection, clutter and clutter suppression, constant false alarm rate (CFAR) processing, algorithms for automatic tracking, and target classification and identification. The book's overall emphasis is on AEW system limitations, developmental trends, and opportunities for improvement.